Penetrating abdominal gunshot wounds caused by high-velocity missiles: A review of 51 military injuries managed at a level-3 trauma center - (:unkn) unknown (My University, 2009)
The aim of this study was to present the outcomes of military penetrating abdominal gunshot injuries, to identify factors that predict morbidity, and to compare the present results with those from two civilian trauma centers. Fifty-one consecutive patients who had suffered high-velocity gunshot wounds to the abdomen were assessed retrospectively. Penetrating abdominal trauma index, the number of injured organs, and the presence of colonic injury were significantly associated with high morbidity by univariate analysis. Multivariate analysis showed that only the number of organs injured and presence of colonic injury were independent predictors of morbidity. Our results showed that military rifle bullets do not cause greater tissue disruption than that found in wounds created by lower-velocity projectiles. The presence of colonic injury and the number of organs injured (more than three) seem to be important predictors of morbidity in penetrating abdominal gunshot wounds caused by highvelocity missiles.
Keywords: Colonic injury; Gunshot wounds; High-velocity missile; Penetrating abdominal trauma index; Penetrating injury